ANALISIS PENGARUH PERSEPSI, SIKAP, PENGETAHUAN DAN TEMPAT KERJA TERHADAP PERILAKU KESELAMATAN KARYAWAN - Putri Agiviana, Anisa; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2015)
The purpose of this research is to analyze on four 4 assessments: 1. Effect of the perception on employee safety behaviour, 2. Effect of demeanour on employee safety behaviour 3. Effect of knowledge on employee safety behaviour, 4. Effect of workplace on employee safety behaviour.This research has been done with techniques like taking random samples with considerations on the population that is quite huge, because it wasn’t possible for the researcher to cover the whole present population, so a representative was formed. Samples in this research are only a part of the whole employee PT. MuliaGlass Container.The result show that test F where the value of significance is 0,000, the coefficient of determination on satisfaction which is shown by r-square is 0,561 that means the customer satisfaction is 56,1% affected by variable of quality of service, price & promotion. Whereas, the rest of the 43,9% is affected because of other variables which were not checked thoroughly by researchers.the factors which not influence safety behaviour was knowledge employee. The result proved the factors which influence safety behaviour were perception, demenour, and workplace.